Comparing Different Equipment and Applications in Pavement Data Collection as Part of Road Management System (European Journal of Formal Sciences and Engineering, 2022)
National roads are the main arteries in road transport infrastructure. Therefore, all agencies or authorities responsible of road infrastructure, pay attention to road management systems. Albania is experiencing an increase in road infrastructure investments and maintenance of this road network. There have been some attempts to establish national and secondary road management systems. These systems attempt to achieve different objectives, such as the provision of an adequate level of service, the preservation of the road infrastructure, etc. A good Road Asset Management System (RAMS), helps to carry out all the actions of inventory, storage and maintenance of road assets as well as, supports the decision-making process. At present, there are several data collection devices and applications that carry out the job efficiently. The purpose of this paper is to present the analysis of the use and comparison of some equipment and Cell Phone Based Systems (MiniROMDAS, PaveProf-V2 and RoadLab_Pro) used for the road pavement data collection, necessary in the calculation of the International Roughness Index (IRI), along the national road network in Albania. The comparison is made, by analyzing the data and results obtained along a 20 km long road segment in Albania, using the various above-mentioned technologies. Also, an overview of the currently available technologies providing information that could assist managers in establishing an appropriate data collection program is given.
Keywords: MiniROMDAS, PaveProf-V2, Road Lab_ Pro, IRI.